P-131 Enhancing medicines safety – small changes lead to big improvements!. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Marley, Kate; Slocombe, Carole; Doyle, Clare; Holland, Graham
Abstract : Introduction: Woodlands Hospice has a transparent approach to incident reporting and staff are encouraged to report near misses. In 2014/15, 76 medicines administration errors were reported, many relating to incomplete documentation. 'Enhancing medicines safety and reducing documentation errors' was chosen as an organisational priority for 2015/16. Actions : Improvements were led by the hospice's Medicines Management Group. A revised medicines management policy was implemented and the annual medicines training programme revised. Inpatient nurses were consulted for their ideas about improvements in medicines safety and 'fact-finding' visits were made to local hospices. All practical ideas were considered and the following were implemented: A 'Woody' sign (based on the hospice rabbit mascot) was designed as an aide-memoire to be placed on bedroom doors to indicate that a medicines-related action needs to be completed e.g. return to administer heparin An additional medicine trolley was purchased to reduce the number of patients on each medicine round A Controlled Drug checklist was devised to ensure daily completion of documentation. Results: Medicines administration incidents for the year 2015/16 reduced from 76 to 25. Additional benefits included: Reduced pressure on nursing staff with more nurses sharing the burden of medicines rounds with round size reducing from 7/8 patients to 5 patients Patients receiving their medicines in a more timely fashion; staff able to spend more time on clinical care 'Woody' is a valuable reminder to staff to return to patients if necessary Controlled Drug documentation is checked and completed daily. Conclusion: Focusing on policy implementation and revising medicines training results in a measurable reduction in documentation errors. However, involving a wider team in developing simple, practical ideas leads to improved medicines administration for patients; reduced pressure on nurses; and better staff morale. Small changes really can lead to big improvements.